(untitled) (Research, Society and Development, 2020)
To generate a long-lasting, competitive advantage, in view of the current scenario of constant transformations and growing competitiveness, it is necessary to develop high performance supply chains that should encompass the entire global market, so that everyone acts in unity. Hence, the value perceived by the end customer becomes higher and higher. To approach the globe as a potential market, however, presents great uncertainties and barriers. Therefore, in addition to a strategic alignment, it is essential to build a multifunctional as well as a multinational team so that the relationship with the supply chain is consistent, close, sustainable and effectively delivers the expected benefits. This article aims to describe, through a focus group, the experience of three large organizations in the implementation and continuous management of suppliers located in low-cost countries. It describes the methodologies and processes that facilitated the strategic alignment of the supply chain, providing sustainable supply, and world-class performance, chains. As a main result, this article provided a view of supply chain management correlating theory and practice, demonstrating the importance of partner development in low-cost countries. As a secondary result, this article presented an analysis of the competitiveness of countries in Eastern Europe and Southeast Asia, in addition to China and India, in three dimensions: business environment, competitiveness in cost and availability of suppliers.